2021
DOI: 10.1590/fst.11020
|View full text |Cite
|
Sign up to set email alerts
|

Difference and characteristics of anthocyanin from Cabernet Sauvignon and Merlot cultivated at five regions in Xinjiang

Abstract: Anthocyanin plays an important role in wine color and quality. The anthocyanin concentration in grapes depends on the variety and is influenced by environmental factors, such as temperature, sunlight, soil, and grapevine practice. In this study, the anthocyanin profiles of two varieties, namely Cabernet Sauvignon and Merlot, from five regions (11 plots) in Xinjiang were examined. The climatic parameters performed noticeable difference between northern and southern of Xinjiang region. Result showed that norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Besides, since berry weight was significantly affected by pruning level and water stress, it can be concluded that the increase was associated with an increase in the skin:flesh ratio. is finding is in line with other authors [40,42,46] whom reported that the increase in total anthocyanins and phenols under heavy pruning was due to an increase in grape berry weight and biochemical response of the anthocyanin and phenol metabolic pathway to the induced signals caused by water stress which led to increase the total anthocyanin and phenolic concentration per gram and contents per berry. In other previous studies [26,41,45], correlation analysis of potential factors contributing to altered metabolism in the anthocyanin pathway showed that color was negatively correlated with vigour indices, canopy density, and stomatal conductance and positively correlated with light penetration into the canopy.…”
Section: Total Anthocyanins and Phenolssupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, since berry weight was significantly affected by pruning level and water stress, it can be concluded that the increase was associated with an increase in the skin:flesh ratio. is finding is in line with other authors [40,42,46] whom reported that the increase in total anthocyanins and phenols under heavy pruning was due to an increase in grape berry weight and biochemical response of the anthocyanin and phenol metabolic pathway to the induced signals caused by water stress which led to increase the total anthocyanin and phenolic concentration per gram and contents per berry. In other previous studies [26,41,45], correlation analysis of potential factors contributing to altered metabolism in the anthocyanin pathway showed that color was negatively correlated with vigour indices, canopy density, and stomatal conductance and positively correlated with light penetration into the canopy.…”
Section: Total Anthocyanins and Phenolssupporting
confidence: 93%
“…In this study, the results indicate that, where water stress does cause an increase in berry anthocyanin and phenol concentration, this is more likely to be due to a physiological response to the berry volume and weight effect. A similar observation [33,41,46] were made that a water stress treatment brought about an increase in anthocyanin and phenolic concentration in the berry skin.…”
Section: Total Anthocyanins and Phenolssupporting
confidence: 64%
See 1 more Smart Citation
“…Malbec is the most widely grown cultivar in Argentina, and its wine generally exhibits intense and uniform color in most of the country regions where it is cultivated [ 33 ]. In contrast, color intensity and the phenolic composition of Merlot wines are strongly influenced by environmental factors, including the growing location [ 34 ]. Pinot Noir is the only cultivar—among these three—that does not produce acylated anthocyanins [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…the synthesis of anthocyanins and procyanidins, and increase the phenolic maturity of grapes (Mota et al, 2021;Zhang et al, 2021). Application of exogenous abscisic acid can increase the content of proanthocyanidins in wine grapes and enhance the oxidative capacity of wine (Xi et al, 2013).…”
Section: Effects Of Foliar Iron Spraying On Cabernet Sauvignon Phenol...mentioning
confidence: 99%